Transformation of Islamic Da'wah in the Digital Era: An Analysis of Ustadz Husain Basyaiban’s Virtual Da'wah Strategy in the Mata Naqra Program - Abir Nabila Asmaul Husna; Zakiyah Romadlany (Social Science Academic, 2026)
Preaching in the digital era has undergone significant transformation, with social media serving as the primary platform for disseminating religious messages. The Mata Naqra program, hosted by Ustadz Husain Basyaiban, offers a distinctive approach to digital preaching by emphasizing systematic and dialogical studies of classical Islamic texts (kitab kuning). This study employs a qualitative design using content analysis of 15 purposively selected video episodes based on their relevance to Islamic learning, dialogical interaction patterns, and preaching strategies. Data were analyzed using thematic analysis through data reduction, coding, categorization, and interpretation to identify patterns of virtual preaching strategies. The findings show that the preaching strategy in Mata Naqra is constructed through three main patterns: strengthening dialogical interaction between preacher and audience, implementing a gradual and systematic learning structure, and contextualizing Islamic messages within the attention economy of digital culture. These patterns form a model of da’wah that balances scientific rationality and spiritual depth, presenting Islam as a contextual and adaptive teaching aligned with contemporary developments. The findings also indicate that digital preaching functions not only as a medium for message dissemination but also as a space for knowledge production that reshapes religious authority and Islamic learning in virtual environments.